From 'Mad Honey' to Hypotensive Agents, the Grayanoid Diterpenes. (September 2016) - Hanson, James R.
The toxicity of Rhododendron species and other members of the Ericaceae which is due to the grayanoid diterpenes, is described. Their structures, biogenesis and biological activity is reviewed.